2021
DOI: 10.1590/1980-549720210017.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle and recommendations in health care among hypertensive and diabetic patients in Brazil, 2019

Abstract: Objective: To estimate prevalence of healthy behaviors among individuals aged 30 years or more, diagnosed with arterial hypertension and diabetes mellitus, using information from the National Health Survey, 2019. Methods: Cross-sectional study with cluster sampling and simple random sampling in three stages. Individuals were aggregated according the following conditions: having arterial hypertension; arterial hypertension only; diabetes mellitus; diabetes mellitus only; arterial hypertension and diabetes mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
7
1
1
Order By: Relevance
“…The data collection methods for each of the CVH metrics are reviewed briefly in Supplemental Table S1 , with the full methodology for each survey described elsewhere. 14 , 16 , 17 , 19 , 20 , 21 , 22 , 26 , 27 , 28 , 29 Data that were considered sufficiently comparable were harmonized ( Supplemental Table S1 ). Harmonized variables were also created for education and current medication use prescribed to reduce BP, glucose, or cholesterol ( Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The data collection methods for each of the CVH metrics are reviewed briefly in Supplemental Table S1 , with the full methodology for each survey described elsewhere. 14 , 16 , 17 , 19 , 20 , 21 , 22 , 26 , 27 , 28 , 29 Data that were considered sufficiently comparable were harmonized ( Supplemental Table S1 ). Harmonized variables were also created for education and current medication use prescribed to reduce BP, glucose, or cholesterol ( Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, unhealthy levels of alcohol consumption increased from 16% to 19% between 2006 and 2019 ( Brasil, 2021 ). Likewise, sedentary lifestyles and unhealthy diets remain common ( Szwarcwald et al, 2021 ). Among Brazilians with hypertension, 76% regularly consume processed foods, and 97.5% have sedentary lifestyles, although they are more likely than average to consume fruits and vegetables and have adequate salt consumption ( Szwarcwald et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brazil’s 2019 National Health Survey study (Pesquisa Nacional de Saude, PNS) shows that more than 80% of individuals reported that their doctor recommended they consume recommended levels of fruits and vegetables, maintain adequate weight, restrict salt consumption, be physically active, and have regular follow-ups ( Szwarcwald et al, 2021 ). However, only 67% and 66%, respectively, reported being recommended not to smoke or drink heavily ( Szwarcwald et al, 2021 ). Little is known about how such recommendations are associated with SES factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The adherence of healthy habits among Brazilian people with the diagnosis of SAH increased in recent years; however, the level of sedentary lifestyle and the consumption of ultra-processed food is still very high. 4 Self-care in the management of SAH is crucial,…”
mentioning
confidence: 99%